The Role of the "Money Tracker: Expense & Budget" Based Financial Recording Application and Business Financial Management on the Quality of Financial Reports in Keripik Singkong Mbak Ros MSME - Situmorang, Yulistira; Nopitasari Manurung; Nadhila Rizky Samura (Jurnal Administrasi Perkantoran, 2025)
This study was conducted to analyze the role of the Money Tracker: Expense & Budget-based financial recording application on the quality of financial reports in Keripik Singkong Mbak Ros MSME. This study used a quantitative method with a series of tests on the research hypothesis. The results showed that the use of the Money Tracker Application had a significant effect on the quality of financial reports partially with a calculated t value of 3.782 > t table value of 1.796 and sig. 0.003 < 0.05. While business financial management partially did not have a significant effect on the quality of financial reports with a calculated t value of 0.628 < t table value of 1.796 and sig. 0.543 > 0.05. However, simultaneously both had a significant effect on the quality of financial reports with a contribution of 57.2%. So it was concluded that the application of the Money Tracker: Expense & Budget-based financial recording application and Business Financial Management had a significant effect on the Quality of Financial Reports of Keripik Singkong Mbak Ros MSME. It is recommended that MSMEs consistently use financial applications and improve their financial management literacy to strengthen their competitiveness. Keywords: Financial Recording; Financial Management; Financial Report Quality; Money Tracker